Structure and Function of Ligand CX3CL1 and its Receptor CX3CR1 in Cancer - Lu, Xinjie (Current Medicinal Chemistry, 2022)
The C-X3-C motif chemokine ligand (CX3CL)1 (also known as Fractalkine) and its receptor CX3CR1 (also known as G-protein coupled receptor 13) are expressed on the membranes of many different cells such as epithelial cells, dendritic cells, smooth muscle cells, and neurons. CX3CR1 is primarily expressed on monocytes, macrophages, dendritic cells, T cells, and natural killer cells. The binding of CX3CL1 to CX3CR1 induces the activation of heterotrimeric G proteins associated with this receptor. In addition, it triggers the signal pathways of MAPK and AKT, which play essential roles in tumour biology. Mechanistically, the CX3CL1-CX3CR1 axis has an antitumour role by recruiting antitumoural immune cells such as NK cells and T cells into the tumour microenvironment to control tumour growth. On the other hand, accumulated evidence indicates that the CX3CL1-CX3CR1 axis also activates a pro-tumoral response. This review will focus on the unique structural biology features of CX3CL1 and CX3CR1, their interactions in tumour inflammatory response, and antitumour effects, which highlights possible potential therapeutic targets.
Keywords: CX3CR1